Factors that influence the purchase of Halal products - Othman, Manisah; Kamarohim, Norazlina (Universiti Putra Malaysia Press, 2016)
This research focuses on the factors that influence purchase of Halal products by consumers in Malaysia that is religiosity, level of confidence, country of origin and attitude. Questionnaires were distributed to 350 consumers in the Klang Valley using convenience sampling. Multiple regressions were used to identify the relationship between purchasing factors and buying decision. The findings showed that religiosity, level of confidence, country of origin and attitude had significant relationship on buying decision. The paper extends the understanding of TRA to newly emerging contexts such as factors that influence the purchase halal products.